Arts Stability and Growth Amid Redevelopment in U.S. Shrinking Cities' Downtowns: A Case Study. (August 2016) - Ganning, Joanna P.
While the relationship between arts businesses and redevelopment has been studied extensively in world-class cities, it remains understudied in weaker market cities. With tight municipal budgets, shrinking cities cannot afford to not understand both the benefits of the arts for downtown redevelopment and the impact of redevelopment on the arts. Using block-level data for a U.S. shrinking city's downtown (St. Louis), this study finds that the arts have neither anchored redevelopment nor been driven out of the downtown by redevelopment. The latter finding signals an opportunity for shrinking cities to harness the benefits of the arts in downtown redevelopment.